2011
DOI: 10.1007/s00027-011-0205-8
|View full text |Cite
|
Sign up to set email alerts
|

Exposure of dissolved organic matter to UV-radiation increases bacterial growth efficiency in a clear-water Alpine stream and its adjacent groundwater

Abstract: In many streams, microbial growth largely relies on terrigenous organic carbon that has been initially stored in soils and that is generally believed to be recalcitrant to microbial metabolism. The various mechanisms that underlie the availability of terrigenous organic carbon as it enters streams remain poorly understood. One possible mechanism can be photodegradation of terrigenous dissolved organic carbon (DOC) upon exposure to sunlight in streamwater. To explore this, we experimentally exposed streamwater,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 41 publications
2
30
0
Order By: Relevance
“…In contrast, the apparent LMW and aromaticity associated with WP correlates with "fresh" biologically produced DOM. 44,45 Thus, by combining these two analytical methods, we are able to substantiate our hypothesis that DOM from anthropogenic input is highly different than naturally derived DOM in term of molecular size, signature, and optical properties. By using this approach, we demonstrate that DOM photoinduced alterations might depend significantly on source and composition.…”
Section: ■ Materials and Methodssupporting
confidence: 62%
“…In contrast, the apparent LMW and aromaticity associated with WP correlates with "fresh" biologically produced DOM. 44,45 Thus, by combining these two analytical methods, we are able to substantiate our hypothesis that DOM from anthropogenic input is highly different than naturally derived DOM in term of molecular size, signature, and optical properties. By using this approach, we demonstrate that DOM photoinduced alterations might depend significantly on source and composition.…”
Section: ■ Materials and Methodssupporting
confidence: 62%
“…Photochemical processing may also make the residual DOC more susceptible to biological utilisation (e.g. Fasching and Battin, 2012). Köhler et al (2002), Moody et al (2013) and Jones et al (this volume) all showed very high rates of DOC loss in samples from peat streams exposed to light, with average DOC removal ranging from 33% to 75% over periods of up to 10 days.…”
Section: Contribution Of Peat Doc Fluxes To Co2 Emissionsmentioning
confidence: 98%
“…The spatial variation is given by the heterogeneity of the environment, as the presence or absence of macrophytes, different depths and the proximity to the borders which increases the impact by the input of allochthonous matter and nutrients by runoff (Wetzel, 1992;Tao, 1998;Obrador and Pretus, 2013). The seasonal variation derives from changes in DOM sources, such as higher input of allochthonous organic matter in the lake during the rainy season and the highest incidence of radiation in spring and summer, which can increase photodegradation rates of CDOM and still favor the lability of the molecules through the breakage part, facilitating microbial degradation (Bertilsson and Tranvik, 1998;Neale et al, 2007;Fasching and Battin, 2012;Catalán et al, 2013). Furthermore, CDOM degradation is also affected by the availability of nutrients throughout the year, a limiting factor for microbial degradation.…”
Section: Introductionmentioning
confidence: 99%